Pengaruh Literasi Digital, Self Regulated Learning, Dan Kompetensi Pedagogik Guru Terhadap Mutu Pembelajaran di SMPN Se Kecamatan Dolopo Madiun - Elma Arma (Excelencia: Journal of Islamic Education & Management, 2023)
The quality of learning is a systemic and synergistic relationship between teachers, students, learning media in producing optimal learning processes and outcomes in accordance with predetermined goals. In accordance with the background that occurred in SMPN in Dolopo District, there were problems with teachers who lacked digital literacy skills, teachers only used learning media with supporting books, there was no integration with existing tools and technology. As well as the control of self-regulated learning that is not optimal. So this is a reflection of the low quality of learning. The quality of learning is influenced by several factors. The most dominant factor is digital literacy, which is the ability to integrate technology into the learning process, self-regulated learning, which is a person's encouragement to organize learning, and teacher pedagogic competence, which is the ability to know how, the teacher's methods in the learning process to achieve goals. This study aims to determine the existence of: (1) To determine the significant effect of digital literacy on the quality of learning in SMPNs throughout the Dolopo sub-district. (2) To determine the significant effect of self-regulated learning on the quality of learning in SMPNs throughout the Dolopo sub-district. (3) To determine the significant effect of teacher pedagogical competence on the quality of learning in SMPNs in Dolopo sub-district. (4) To determine the significant effect of digital literacy, self-regulated learning and teacher pedagogic competence on the quality of learning in SMPNs in Dolopo sub-district The research method uses quantitative methods with an ex post facto approach with descriptive statistical research types. There are four variables that influence each other in this study, namely digital literacy, self-regulated learning, and pedagogical competence as independent variables and learning quality as the dependent variable. data collection technique using a questionnaire. Data analysis used simple linear regression analysis and multiple linear regression. The population of this study were 92 teachers and the sample technique used was saturated sampling with 92 people. Based on data analysis, it was found: (1) there was an influence of digital literacy (X1) on the quality of learning (Y) in SMPNs in Dolopo sub-district. (2) there is an effect of self-regulated learning (X2) on the quality of learning (Y) in SMPNs throughout Dolopo sub-district. (3) there is an effect of teacher pedagogic competence (X3) on the quality of learning (Y) in SMPNs in Dolopo sub-district. (4) the influence of digital literacy (X1), self-regulated learning (X2) and teacher pedagogic competence (X3) on the quality of learning (Y) in SMPNs in Dolopo sub-district. Keywords influence, digital literacy, self-regulated learning, teacher pedagogical competence, learning quality.